Study on the structure characterization and moisturizing effect of Tremella polysaccharide fermented from GCMCC5.39 - Meng Yang; Zilong Zhang; Yan He; Chengliang Li; Jinmei Wang; Xia Ma (Food Science and Human Wellness)
The structure and moisture retention of Tremella polysaccharide fermented from GCMCC5.39 (FTP) were evaluated. After UV, infrared spectrum analysis, HPAEC-PAD, HPSEC and 1 D NMR analysis, the composition of the purified FTP was determined. Purified components of fermented Tremella polysaccharide (FTPS) was made of galactose, mannose, glucose, galactosmine, glucosamine, and contain a large amount of hydroxyl, carbonyl and amino groups. FTPS was α -neutral pyranose without uronic acid. FTPS-1 and FTPS-2 were obtained after purification by DEAE-Sepharose Fast Flow Column. The molecular weights of FTPS-1 and FTPS-2 were 25 722 and 177 263 Da. FTPS-2 had a better ability to prevent moisture loss, and the optimal moisture retention period was 0–4 h. FTPS-2 could significantly increase the moisture content of the skin epidermis and showed a dose-concentration relationship. The effect of FTPS-2 on the expression of different moisturizing genes was evaluated in a human skin keratinocyte model. The results showed that FTPS-2 has no cytotoxicity, and could significantly promote AQP3, TGM1, CASP14, HYAL2, FLG gene expression level in HaCaT cells. It has the most significant influence at HYAL2 protein expression on 50 μg/mL.